PENINGKATAN KEMAMPUAN PEMAHAMAN MATEMATIS SISWA KELAS VIII SMP PASUNDAN 9 BANDUNG PADA MATERI PERSAMAAN GARIS LURUS DENGAN MENGGUNAKAN PENDEKATAN KONSTEKTUAL - Saida Manalu, Arpin Chronika; Afrilianto, M (IKIP Siliwangi, 2020)
This research is a classroom action research with descriptive qualitative method, which aims to ilustrate how improved students mathematical understanding abilities when using Contextual Teaching and Learning (CTL) approach to the material of straight line equations. The subjects of this study is 32 students of class VIII-C Junior High School Pasundan 9 Bandung. The instruments used in this study is 5 essay questions that referref to indicators of mathematical understanding ability that is given at the beginning of learning and the end of learning, which is then analyzed by calculating the average of each question indicator. The result of this study indicate that students mathematical understanding ability can be improved using a contextual teaching and learning approach.